The Effect of Aerobic Exercises on Glycosylated hemoglobin and Blood Pressure and Fat in Preparatory School Female Students with Type One Diabetes - Saeed, Wasan; Majed, Fatema (Journal of Physical Education, 2023)
The study aimed at designing aerobic exercises for preparatory female school students with type one diabetes as well as identifying the effect of aerobic exercises on glycosylated hemoglobin HBA1C. The study also aimed at identifying the effect of aerobic exercises on blood pressure as well as on fat (Lipoproteins) in female students with type one diabetes. The researcher used the experimental method on (10) female preparatory students aged 14 – 18 years old with type one diabetes. The results showed improvement in glucose level in the blood, reduced insulin resistance through physical exercises especially aerobic exercises. The researcher concluded that balance between insulin treatment and food can give good results along with aerobic exercises that increased glucose that is irreplaceable.